Effects of acetyl‐L‐carnitine and methylcobalamin for diabetic peripheral neuropathy: A multicenter, randomized, double‐blind, controlled trial. Issue 5 (28th March 2016) - Li, Sheyu; Chen, Xiang; Li, Qianrui; Du, Juan; Liu, Zhimin; Peng, Yongde; Xu, Mian; Li, Qifu; Lei, Minxiang; Wang, Changjiang; Zheng, Shaoxiong; Zhang, Xiaojuan; et al.
Abstract: Aims/Introduction: To assess the efficacy and safety of acetyl‐L‐carnitine (ALC) on diabetic peripheral neuropathy compared with methylcobalamin (MC). Materials and methods: This was a multicenter, randomized, parallel‐group, double‐blind, double‐dummy, positive‐controlled, non‐inferior phase II clinical trial. Diabetic patients with abnormal nerve conduction test results were randomized in a 1:1 ratio to receive oral ALC 500 mg t.i.d. or MC 0.5 mg t.i.d. for 24 weeks. The neuropathy symptom score, neuropathy disability score and neurophysiological parameters were measured during follow up. Results: A total of 232 patients were randomized (ALC n  = 117, MC n  = 115), 88% of which completed the trial. At week 24, patients from both groups had significant reductions in both neuropathy symptom score and neuropathy disability score with no significant difference between two groups (neuropathy symptom score reduction: ALC vs MC 2.35 ± 2.23, P  < 0.0001 vs 2.11 ± 2.48, P  < 0.0001, intergroup P  = 0.38; neuropathy disability score reduction ALC vs MC 1.66 ± 1.90, P  < 0.0001 vs 1.35 ± 1.65, P  < 0.0001, intergroup P  = 0.23). Neurophysiological parameters were also improved in both groups. No significant difference was found between groups in the development of adverse events. Conclusions: ALC is as effective as MC in improving clinical symptoms and neurophysiological parameters for patients with diabetic peripheral neuropathy over a 24‐week period with good tolerance. Abstract : This multicenter, randomized, double‐blinded, controlled trial suggested acetyl‐L‐carnitine (ALC) is as effective as methylcobalamin in improving clinical symptoms and neurophysiological parameters for patients with diabetic peripheral neuropathy (DPN) with good tolerance.